Implikasi Teori Emanasi dalam Konsep Kepemimpinan al-Farabi - Fuad Muhammad Zein (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2023)
This research discusses the implications of the concept of emanation in the leadership theory of al-Farabi, one of the great philosopher in the Islamic philosophical tradition. The background to the problem raised is how the theory of emanation, as one of the key concepts in al-Farabi's thought, is not only related to the way God created His creation but also has implications for the building of his philosophical views, especially the issue of a state leader. The research results show that al-Farabi's concept of emanation influences his view of ideal leadership, where a perfect leader is one who is able to manifest divine attributes through wisdom, justice and benevolence. This leader is not only a political ruler, but also a spiritual guide who is able to lead society to intellectual and moral perfection. The implication of these findings is that effective leadership in al-Farabi's perspective requires integration between spiritual and temporal aspects, which can be the basis for the development of contemporary leadership models in Muslim societies.